Synthesis and Characterization of Some Metal Complexes of [N-(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol4-ylcarbamothioyl) acetamide] - Sarhan, Basima M.; Lateef, Sajid M.; Waheed, Enass J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new  ligand  [N- (1,5- dimethyl -3- oxo- 2 â€“ phenyl - 2 ,3 â€“ dihydro -1H- pyrazol -4ylcarbamothioyl) acetamide] (AAD) was synthesized by reaction of acetyl isothiocyanate with 4-aminoantipyrine, The ligand was characterized by micro elemental analysis C.H.N.S., FT-IR ,UV-Vis and 1H-13CNMR spectra, some transition metals complex of this ligand were prepared and  characterized by FT-IR, UV-Vis spectra, conductivity measurements, magnetic susceptibility and atomic absorption. From the obtained results the molecular formula of all prepared complexes were [M(AAD)2(H2O)2]Cl2  (M+2 = Mn, Co, Ni, Cu, Zn, Cd and Hg),the proposed geometrical structure for all complexes were octahedral.